Adaptation Patterns of Street Vendors in Yahim District, Jayapura City in Economic Recovery During the Covid-19 Pandemic - Maga, La; Timisela, Stephanny Inagama; Titalessy, Pisi Bethania; Antoh, Agustina Ester; Mulyono, Herlina Irianti; Matuan, Fetronela (Journal of International Conference Proceedings, 2023)
The Covid-19 pandemic not only has an impact on health, but also has an impact on income levels for street vendors (PKL) in the Yahim District, Jayapura City. Even though street vendors continue to run their businesses, they are always controlled by the government. People are obliged to follow the regulations set by the government on the other hand they must fulfill their family's economic needs. Society must be able to adapt to changing social environmental conditions. The aim of this research is to analyze the forms of active adaptation and passive adaptation carried out by street vendors during the Covid-19 pandemic. There are several forms of active adaptation carried out by street vendors, namely continuing to run the business but with lower production volumes, continuing to run the business with the risk of receiving sanctions from the government, reducing expenses for household needs, and prioritizing basic needs in the form of food, education and health. Meanwhile, the form of passive adaptation carried out by street vendors is temporarily closing their businesses in accordance with government regulations, utilizing remaining capital or profits from businesses run before the Covid-19 pandemic, and utilizing savings.